Factor potential implementation of augmented reality (AR) among developer in Malaysia - Nur Rabiatul Adawiyah, Hasim (2018)
Augmented Reality (AR) is a new technology that lies between virtual and real world as it computer-generated. It may not be as exciting as a virtual reality such as rollercoaster ride however augmented reality has element which brings out virtual element into the real world enhancing things we see, hear and feel. Based on the literature exploration, AR in Malaysian industry a bit behind compared other develop country in aspect knowledge due to lack knowledge. This paper are to study the factor potential implementation of Augmented Reality in developer. The first objective of this study is to study AR applications uses in Malaysia in modelling building. The second objective is to identify the potential factor implementation of AR The third objective which is will contribute to the outcome of this study is to analyse the most influence factor potential of implementation AR usage for house modelling. Questionnaires survey was carried out to gain objective which the questionnaires are distributed to random respondent with different background. The questionnaires have 5 segments represent each possible factors potential implementation of AR which is visualization, costing, time, knowledge, software and hardware. Data are analyzed by using RII analysis method. In coherent result obtained, the most influence factor to implement AR in developer industry is visualization produce by AR by reason of interest 3D model display on their smartphone devise by reason of respondent able to engaged with the house design further than viewing the 2D floor plan even more interesting and immersive way in AR technology.